Safeguard plan management for heritage buildings: development of a spatial information system (2011)
This paper explains the methodology and criteria used in the development of a new tool for the management of a safeguard plan for historic buildings in Avila, which is a Spanish World Heritage City. As a result of a first approximation, there are many requirements to take into account: completeness, interactivity, ease of use, modularity, and low costs. Due to the characteristics of the information (spatially located, heterogenic, and provided in different formats) we consider it indispensable to create a spatial information system that is qualifiedfor organizing all available multimedia digital information (2-D images, panoramas, graphics, text documents, and music). While the mainobjective of this study is to provide a simple tool for the management of historic and artistic heritage in the form of a safeguard plan, the features of the tool created here open up new possibilities for other uses in the future.